Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1986
DOI: 10.1111/j.1365-2265.1986.tb01708.x
|View full text |Cite
|
Sign up to set email alerts
|

An Analogue of Met‐enkephalin Attenuates the Pituitary‐adrenal Response to Ovine Corticotrophin Releasing Factor

Abstract: The met-enkephalin analogue, DAMME, suppresses the pituitary-adrenal axis in normal subjects; it is not clear whether this occurs at the level of the pituitary or above. We therefore administered synthetic ovine corticotrophin releasing factor (CRF-41) 100 micrograms i.v. to a group of normal male subjects, with or without pretreatment with DAMME 250 micrograms i.v., and monitored the response of plasma ACTH and serum cortisol. CRF-41 caused a marked stimulation of ACTH and cortisol release, but this was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 37 publications
4
9
0
Order By: Relevance
“…This hypothesis is also compatible with reports on the effects of morphine and DAMME on responses to either CRH-41 or vasopressin alone: DAMME and mor phine block the rise in cortisol induced by CRH-41 [29][30][31], while DAMME will inhibit the cortisol response to vasopressin [32]. On the current scheme, it is envisaged that exogenous opiate agonists inhibit both CRH-41 and vasopressin, hence, the response to either peptide would be suppressed by the ab sence of its synergising fetor.…”
Section: Discussionsupporting
confidence: 80%
“…This hypothesis is also compatible with reports on the effects of morphine and DAMME on responses to either CRH-41 or vasopressin alone: DAMME and mor phine block the rise in cortisol induced by CRH-41 [29][30][31], while DAMME will inhibit the cortisol response to vasopressin [32]. On the current scheme, it is envisaged that exogenous opiate agonists inhibit both CRH-41 and vasopressin, hence, the response to either peptide would be suppressed by the ab sence of its synergising fetor.…”
Section: Discussionsupporting
confidence: 80%
“…While there are some reports that have shown that loperamide poorly penetrates the blood-brain barrier [9,10], we have presented arguments for loperamide suppressing ACTH secretion in man by a possible suprapituitary site of ac tion, although an additional pituitary site could not be excluded [11]. These results parallel the findings obtained with a number of u-opiate agonists with regard to ACTH secretion in man [12][13][14],…”
Section: Introductionsupporting
confidence: 79%
“…The results of CRH studies indicate an inhibition of the first phase of the peptide after loperamide and resemble the findings obtained in normal subjects with CRH given after morphine [19] and after the met-enkephalin analog FK 33-824 [12], However, the present data do not agree with previous findings showing that, in normal subjects, FK 33-824 in duces an almost complete inhibition of ACTH secretion after LVP [6] and CRH [3[. These discrepancies may be ex plained by: (i) differences in the study protocol; (ii) a hig her sensitivity, in patients with Addison's disease to ACTH modulating agents, as a consequence of lacking cortisol feedback mechanism: (iii) the different properties of the opioids used: in fact, low doses of naloxone are able to re verse the effects of loperamide on ACTH secretion [4], while higher doses are required to counteract the inhibitory action of FK 33-824 [2],…”
Section: Discussionsupporting
confidence: 68%
“…Many in vitro [5,19] and in vivo studies [10,18] have indicated that opioids act at the hypo thalamic level, although an effect on pituitary corticotrophs has been also shown [14], In man, a direct influence on the pituitary gland has been hypothesized [6], while an interac tion of FK 33-824 [12] and morphine [19] with hypothalamic modulators of corticotropic secretion has been also sugges ted. The observation that loperamide is unable to suppress the ACTH responses after both CRH and vasopressin suggest a suprapituitary action.…”
Section: Discussionmentioning
confidence: 99%